Simultaneous determination of procalcitonin and interleukin-6 in human serum samples with a point-of-care biosensing device - Tsounidi,D.; Tsaousis,V.; Xenos,N.; Kroupis, C.; Moutsatsou, P.; Christianidis,V.; Goustouridis,D.; Raptis,I.; Kakabakos,S.; P. Petrou (Talanta, 2023)
The simultaneous determination of two inflammatory diseases biomarkers, namely procalcitonin (PCT) and interleukin-6 (IL-6), in human serum samples employing a Point-of-Care device based on Multi Area Reflectance Spectroscopy is presented. Dual-analyte detection was achieved using silicon chips with two silicon dioxide areas of different thickness, one functionalized with an antibody specific for PCT and the other with an antibody specific for IL-6. The assay included reaction of immobilized capture antibodies with mixtures of PCT and IL-6 calibrators with the biotinylated detection antibodies, streptavidin and biotinylated-BSA. The reader provided for the automated execution of the assay procedure, as well as for the collection and processing of the reflected light spectrum, the shift of which is correlated to analytes concentration in the sample. The assay was completed in 35 min and the detection limits for PCT and IL-6 were 2.0 and 0.01 ng/mL respectively. The dual-analyte assay was characterized by high reproducibility (the intra- and inter-assay coefficients of variation were less than 10% for both analytes) and accuracy (the percent recovery values ranged from 80 to 113% for both analytes). Moreover, the values determined for the two analytes in human serum samples with the assay developed were in good agreement with the values determined for the same samples by clinical laboratory methods. These results support the potential of the proposed biosensing device application for inflammatory biomarkers determination at the Point-of-Need
IS - 1873-3573 (Electronic) IS - 0039-9140 (Linking) LA - eng PT - Journal Article RN - 0 (Antibodies, Immobilized) RN - 0 (Biomarkers) RN - 0 (Interleukin-6) RN - 0 (Procalcitonin) SB - IM
Keywords: Antibodies,Immobilized; Biomarkers; Biosensing Techniques; Blood; chemistry; Humans; Immunoassay; Interleukin-6; methods; Point-of-Care Systems; Procalcitonin; Reproducibility of Results